Scoping Review of Existing Evaluations of Smokeless Tobacco Control Policies: What Is Known About Countries Covered, Level of Jurisdictions, Target Groups Studied, and Instruments Evaluated?. Issue 9 (16th April 2022) - Forberger, Sarah; Khan, Z; Ahmad, F; Ahmed, F; Frense, J; Kampfmann, T; Ullah, S; Dogar, O; Siddiqi, K; Zeeb, H
Abstract: Objective: The implementation of smokeless tobacco control policies lags behind those for smoking. This scoping review summarizes the studies that evaluated public policies on smokeless tobacco regulation (SLT) and provides an overview of the jurisdictional level, target groups, and policy instruments. Methods: Seven databases were systematically searched for studies reporting on public policies regulating SLT. Two reviewers independently screened all studies. Data extraction was performed using a predefined extraction form. Extraction was replicated for 10% of the identified studies for quality assurance. A narrative synthesis of the included studies was used to analyze and interpret the data. The protocol was published beforehand with the Open Science Foundation (OSF). Results: Fourty articles comprising 41 studies were included. Most of the studies reported in the articles were conducted in the United States ( n = 17) or India ( n = 14). Most studies reported outcomes for students ( n = 8), retailers/sellers ( n = 8), and users/former users ( n = 5). The impact of public policies on smokeless tobacco use, in general, was most frequently assessed ( n = 9), followed by the impact of taxes ( n = 7), product bans ( n = 6), sales/advertising bans near educational institutions ( n = 4), and health warnings ( n = 3) on consumer behavior. Conclusions: There are significant gaps in the evaluation of smokeless tobacco regulation studies that need to be filled by further research to understand the observed outcomes. WHO reporting on Framework Convention on Tobacco Control (FCTC) implementation should be linked to studies evaluating smokeless tobacco control measures at all levels of jurisdictions and in countries not members of the WHO FCTC or do not provide data. Implication: Large gaps in the evaluation of SLT control policies exist. For some countries, WHO FCTC evaluations are available for different levels of jurisdictions. In countries with a strong federal structure, there is a lack of data beyond the national level to provide a more detailed look at compliance, indirect effects, or implementation gaps. More research is needed at all levels of jurisdictions, which add to the work of the WHO to understand what works for which target group, how the different levels of jurisdiction interact, how the real-world context can be incorporated, and what indirect effects may occur.